Understanding How Rural Communities Utilize Social Capital to Strengthen Livelihoods and Institutions: Insights from Tasikmalaya Regency, Indonesia - Rustanto , Bambang; Irianti, Decky; Kartika, Tuti; Yuliani, Dwi; Istyawan, Aryohaji (LPPM Universitas Jambi, 2026)
Village development in Indonesia depends not only on material assistance but also on the quality of social relationships that enable residents to cooperate and access external resources. This qualitative case study examines how the community of Sukarame Village, Tasikmalaya Regency, utilizes social capital (bonding, bridging, and linking) to support rural community development. Data were collected through in-depth interviews, direct observation, and document review involving 17 participants from agricultural and non-agricultural livelihoods, village institutions, and community leadership. The data were analyzed thematically using source and technique triangulation. Findings show that bonding social capital, rooted in kinship, religious gatherings, and the pipiti communal fund, provides social solidarity. Bridging social capital manifests through business networks spanning embroidery, sequin work, vehicle repair, inland fish farming, tofu-tempeh production, livestock, and external marketing. Linking social capital develops through cooperation among residents, village government, technical agencies, banks, and social programs, while local institutions serve as operational spaces where these assets are practiced and sustained. The novelty of this study demonstrates how rural communities actively convert interdependent social capital into productive use, expanding both livelihoods and institutional access. Ultimately, rural community development is most effective when government programs reinforce, rather than replace, existing social capital for sustainable empowerment.